The Cityscape in the Contemporary African-American Urban Novel - Stulov, Yuri (Respectus Philologicus, 2013)
This paper discusses the cityscape as an essential element of African American fiction. Since the time of Romanticism, the city has been regarded as the embodiment of evil forces which are alien to human nature and radiate fear and death. For decades, African-Americans have been isolated in the black ghettos of major American cities which were in many ways responsible for their personal growth or their failure. Often this failure is determined by their inability to find their bearings in a strange and alien world, which the city symbolizes. The world beyond the black ghetto is shown as brutal and terrifying, while the world inside is devoid of hope. Crime, vandalism, poverty, overcrowding, and social conflicts turn out to be the landmarks of big cities, because the people who migrate to them and make up most of their population are also the poorest and least adapted to urban life: they have lost their roots, and feel displaced in the anonymous urban society. A number of African-American novels depict protagonists who are unable to adapt to life in a big city, and end in degradation and misery. James Baldwin’s novels are among the most representative. His disordered and dislocated characters are products of the external world of the city of the machine age, and as such they are characteristic of all African-American fiction. This paper analyzes some of the recent black novels that reverberate with Baldwin’s ideas.